Anthropomorphic Figurines with Hunched Backs and Deformed Breasts in Kodjadermen–Gumelniţa–Karanovo VI Culture - Stavreva, Vanya (Archaeologia Lituana, 2022)
A number of unusual anthropomorphic figurines featuring hunched backs and conical protrusions on their chests have been unearthed in several settlements that belong to the area of the Kodjadermen–Gumelniţa–Karanovo VI culture. The figurines have not been subject to a special study in scholarly literature so far and hence, no attempt at their interpretation has ever been made.The study discusses the possibility that these unusual images reflect a physical disability caused by Pott’s disease. Anthropologic research on skeletal remains of the Eneolithic population of Europe has established pathological changes that are consistent with this disease. Its cause, Mycobacterium tuberculosis, has been identified also through biomolecular study of human bones, which confirms the spread of tuberculosis in this period. The author furthermore argues about the possible use of this type of figurines in magic rituals. In addition, some ethnographic data is supplied for the use of clay anthropomorphic images in health-bringing and healing rites.
Keywords: anthropomorphic figurines; eneolithic; tuberculosis; magic rituals